Stimulating angiogenesis into biomaterials through the delivery of growth factors - Schmidt, Christian Alexander Peter (Division of Cardiology, 2017)
lschemic disease in form of ischemic heart disease (IHD), ischemic stroke and peripheral arterial disease (PAD) due to atherosclerosis represents a massive clinical and economic burden to healthcare and is currently the number one cause of death in the world. Treatment modalities for peripheral arterial disease include bypass surgery involving autologous vein or synthetic materials such as ePTFE. Long term patency of small diameter vascular grafts used for infra-inguinal reconstructions, however, is below 50 % 5 years after implantation. Therefore, novel vascular graft concepts and materials are needed. The concept of transmural in vivo endothelialisation of vascular grafts holds great promise for increasing long term patency. To achieve complete luminal endothelial cell coverage and optimal integration of the porous synthetic graft material into the host tissue, transmural ingrowth of tissue and vasa vasorum might have to be facilitated. Since VEGF1ss and PDGF-BB are growth factors known to stimulate and consolidate angiogenesis, this PhD thesis hypothesized, that neovascularisation of porous polyurethane (PU) can be increased by delivery of vascular endothelial growth factor (VEGF1ss) and platelet derived growth factor (PDGF-BB). To prove this hypothesis, subcutaneous implantation of PU discs was established as a valid, reproducible, relatively simple and quantifiable neovascularisation model. Three different ways of growth factor delivery were investigated. The gene encoding for human VEGF15s was cloned into the genome of adeno associated viruses (AAV), which served as a vector for gene transduction of autologous wound healing cells in vivo using the "Gene Activated Matrix" approach. Genetically modified matrix embedded AAV-VEGF155 was loaded into porous PU and transduced autologous ingrowing wound cells. In contrast to the excellent transduction efficiency in myocytes, AA V showed a poor tropism for wound healing cells. The second approach to increase neovascularisation into porous PU was the surface modification of PU by covalent attachment of nitrous acid degraded heparin. Neovascularisation into the biomaterial was increased by 77 % after 10 days of subcutaneous implantation. Since certain angiogenic growth factors show a high affinity for heparin, additional loading of heparin surface modified PU with VEGF165 increased neovascularisation even further up to 115 % at 10 days compared to control. Dual growth factor delivery of VEGF 165 and PDGF-BB not only initiated increased vascularisation of porous PU, but also created a stable vascular network 2 months after implantation. In contrast, PU loaded with VEGF165 alone showed regression of total vascular area of 61 % compared to vascular area at 10 days. Thirdly, to study the effects of controlled, prolonged growth factor delivery, a "Neovascularisation Construct" was developed which was implanted subcutaneously in rats. The construct consisted of an osmotic mini pump and a tube of porous PU lined with ePTFE, into which a defined amount of VEGF16s was pumped for 10 days. After implantation, granulation tissue was growing into the pores of the PU and neovascular area was increased up to 265 % compared to PBS control. Furthermore, using different growth factor concentration, a dose dependency was shown. In addition, this thesis investigated the functional perfusion of the micro vascular network growing into PU by four different vascular quantification techniques. lntravital perfusion with biotinylated lycopersicon esculentum followed by microscopical analysis, vascular corrosion casting quantified by scanning electron microscopy as well as the novel micro-CT analysis of silicone rubber perfused vessels were compared to conventional immunhistochemical analysis of endothelial cells by CD31. Interestingly, PBS perfused "Neovascularisation Constructs" showed a relatively poor perfusion; therefore CD31 immunohistochemistry "overestimated" functional neovascularisation 3 fold. All perfusion techniques indicated a strong effect of VEGF 165 delivery on vessel perfusion (10 to 20 fold increases of vascular area and volume compared to PBS control). Micro-CT scanning was shown to be an excellent tool to study micro vascular networks in a three-dimensional fashion across the whole length of the sample in a limited amount of time and to provide reliable and reproducible data on vessel density, vascular volume, and connectivity. Since resolution is still limited today to about 10 μm using a commercially available bench top scanner, this new technology still needs to be complemented by immunohistochemistry and perfusion studies such as lectin perfusion and corrosion casting. In summary, the induction of neovascularisation was achieved by heparin surface modification alone, which was even increased through additional delivery of growth factors into the biomaterial PU. The development of a stable micro vascular network at 2 months was achieved and the functionality was shown using four different, independent techniques including the novel micro-CT scanning of neovascularisation into biomaterials. Towards the development of an in vivo, spontaneously and transmurally endothelialising vascular graft with superior long-term patency further investigations are necessary. As an initial step, increased spontaneous neovascularisation of the possible graft material polyurethane was achieved. Future steps are clearly indicated to study the translation of increased neovascularisation of the biomaterial polyurethane towards increased endothelialisation in a vascular graft model.